Function Forecasting Sales of Row Materials with Least Square Method (Study Case PD Surabraja Jamblang, West Java Indonesia) - Nurhana Dhea Parlina (JURISMA : Jurnal Riset Bisnis & Manajemen, 2016)
Aim of this study was to determine the method of quantitative sales forecasting for needed raw materials. Population in this study are sales data PD Surabraja in Jamblang West Java from January 2012 to September 2015. This study using purposive sampling and data collection by observation. Data were analyzed using the least squares method. The study found that there are effects sales forecasting on raw materials. This research is relation of sales forecasting and real forecasting are most weak from value of coefficient correlation - 0.0012. This means value of correlation result negative close score 0 so relation of sales forecasting with from least square method to determine raw material method in PD. Surabradja in period of time certaintly for the future. Forcasting SJMBDUS in month of October 2018 as many 14,32 kg.